Work programme for a five-year period (1994-1998) (UN. ECLAC SantiagoCL, 1993)
Focuses on projects such as the establishment of a technical extension project; assisting CCST focal points to develop individual science and technology work programmes; programme to improve the teaching of science and mathmetics at the primary school level; the history of scientific and technological development in the Caribbean; and, community development and improvement through the application of science and technology : preliminiary survey.
DC